2021
DOI: 10.1021/acsanm.1c00074
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Gold Nanoparticles as an Active Layer for Mercury Vapor Detection at Room Temperature

Abstract: Nanomaterials such as gold nanoparticles employed as solid-state sensors have attracted attention in recent years due to their ability to detect poisonous elements in the indoor/outdoor environment. Herein, chemoresistive sensors based on gold nanoparticles (AuNPs) functionalized with mixed thiol ligands were tested as sensing materials. Specifically, the electrical response of gold nanoparticles-based sensors was tested against Hg0 vap, H2S, SO2, NH3, and relative humidity (RH) at room temperature. Gold nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(103 reference statements)
1
7
0
Order By: Relevance
“…On the basis of Au NPs, a series of analysis routes, such as electrochemical, electrochemiluminescent, chemiresistive, field-effect transistor, surface-enhanced Raman scattering, fluorescence, and light-scattering assays, as well as other colorimetric methods, were established through various recognition and response mechanisms (Table S1). In comparison to their performances of mercury measurements, the developed allochroic hydrogel assay exhibits the merits of simple and rapid operation, ideal sensitivity, high selectivity, and high-throughput characteristics, integrated with the function of mercury enrichment and material reutilization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the basis of Au NPs, a series of analysis routes, such as electrochemical, electrochemiluminescent, chemiresistive, field-effect transistor, surface-enhanced Raman scattering, fluorescence, and light-scattering assays, as well as other colorimetric methods, were established through various recognition and response mechanisms (Table S1). In comparison to their performances of mercury measurements, the developed allochroic hydrogel assay exhibits the merits of simple and rapid operation, ideal sensitivity, high selectivity, and high-throughput characteristics, integrated with the function of mercury enrichment and material reutilization.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Among them, the peaks at 161.5 and 162.6 eV were attributed to sulfur atoms covalently bound to gold atoms. 48,49 These results confirmed that RRP-MPBA was attached to the surface of the GNRs by the formation of a Au− S bond.…”
Section: Uv−vis Spectral Analysis Of Rrp-mpba-gnrsmentioning
confidence: 99%
“…In addition, gold nanomaterials such as nanoparticles, nanoclusters, nanowires, and nanotubes were employed in electrochemical (bio)sensing areas, not only for their high conductivity and compatibility, but also for their high surface-to-volume ratios [38][39][40][41][42][43].…”
Section: Electrochemical Chemosensors and Biosensors: Definitions Techniques And Sensing Materialsmentioning
confidence: 99%